Virtue Revisited in the Novels of Doris Lessing - Arikan, Seda (Taylor and Francis, 2024)
The ethical approaches to literature have come into prominence in the twentieth century, calling for a ‘turn to ethics’ in the studies of humanities, in general, and literary studies, in particular. By leading the ethical turn in literature, many theorists proposed a moral-oriented approach to literature, which is still a significant part of literary criticism. The ethical turn in literature has changed the spirit of literary criticism in the direction of virtue and value-based approaches. In this respect, this study scrutinises Doris Lessing’s novels in light of virtue ethics in general and ‘virtue politics,' ‘care ethics,' and ‘Sufi virtue ethics’ in particular. Lessing’s connection to virtue ethics, which is implicitly or explicitly reflected in her novels, is examined by giving the panorama of ethical movements whose common point is virtues. This study asserts that Lessing implements an ethical concern in her novels, which is based on her own understanding of virtue ethics. © 2025 Seda ARIKAN.